Analysis of Project Based Learning Integrated with Ethno-STEM on Students' Critical and Creative Thinking Skills - Ariyatun Ariyatun (Journal of Educational Chemistry (JEC), 2021)
Critical and creative thinking is a component of 21st-century skills that meet the needs of the educational process. Moreover, local wisdom learning, which is closely related to scientific concepts, also needs to be emphasized. This study aimed to analyze students' critical and creative thinking skills by implementing Project-Based Learning Integrated with Ethno-STEM. This study was a case study with a One-Shot Case Study design. Its subjects were 36 students of class XI Science Program of SMA Negeri 1 (State Senior High School 1) Weleri as many as 36 students. The data collection used a test instrument validated by experts and gained a Cronbach Alpha score of 0.72. Based on the results of data analysis, it revealed that students' critical thinking skills included good criteria with the highest achievement in the aspect of providing simple explanations. In contrast, students' creative thinking abilities belonged to good criteria with the highest achievement in flexibility, giving various interpretations of an image, story, or problem. In conclusion, Project-Based Learning integrated with Ethno-STEM can train students' critical and creative thinking skills.